Floristic diversity associated to andean Pomacocha and Habascocha Lakes, Junín, Peru - Flores, Mercedes (2005)
A study of the floristic diversity of the surroundings of Lakes Pomacocha and Habascocha (4350 - 4550 m, 11°45’-11°48’S and 75°12’-75°15’W), Province of Concepción, Junín, Peru, reported a total of 29 families, 64 genera, and 100 species. Poaceae was the most diverse family (25%), followed by Asteraceae (24%) and Gentianaceae (6%). The floristic composition of the Puna of Concepción was compared to those of other localities of the Peruvian Puna.